2019
DOI: 10.1002/ece3.5685
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics reveals unique and shared effects of urbanization for two sympatric pool‐breeding amphibians

Abstract: Metapopulation‐structured species can be negatively affected when landscape fragmentation impairs connectivity. We investigated the effects of urbanization on genetic diversity and gene flow for two sympatric amphibian species, spotted salamanders (Ambystoma maculatum) and wood frogs (Lithobates sylvaticus), across a large (>35,000 km2) landscape in Maine, USA, containing numerous natural and anthropogenic gradients. Isolation‐by‐distance (IBD) patterns differed between the species. Spotted salamanders showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 142 publications
(196 reference statements)
2
8
1
2
Order By: Relevance
“…When analysing contemporary barriers to gene flow, landscape genetic studies must take into account the spatial scale of sampling relative to habitat suitability and disturbance (Epps & Keyghobadi, 2015; Manel, Schwartz, Luikart, & Taberlet, 2003). Although we did not detect contemporary barriers to gene flow, studies with other amphibians that sampled at scales comparable to ours found genetic signatures of land cover disruption (Homola, Loftin, & Kinnison, 2019; Zancolli, Rödel, Steffan‐Dewenter, & Storfer, 2014). Specifically, our sampled populations, which cover the entire species’ known range, showed enough variation in the seven land cover classes between population pairs (Figure 1c).…”
Section: Discussioncontrasting
confidence: 61%
“…When analysing contemporary barriers to gene flow, landscape genetic studies must take into account the spatial scale of sampling relative to habitat suitability and disturbance (Epps & Keyghobadi, 2015; Manel, Schwartz, Luikart, & Taberlet, 2003). Although we did not detect contemporary barriers to gene flow, studies with other amphibians that sampled at scales comparable to ours found genetic signatures of land cover disruption (Homola, Loftin, & Kinnison, 2019; Zancolli, Rödel, Steffan‐Dewenter, & Storfer, 2014). Specifically, our sampled populations, which cover the entire species’ known range, showed enough variation in the seven land cover classes between population pairs (Figure 1c).…”
Section: Discussioncontrasting
confidence: 61%
“…For instance, effective estimates of migration surfaces (EEMS; Petkova et al, 2016) can visualize where genetic similarity by migration decays faster than expected by IBD, thus highlighting areas of reduced gene flow at geographic boundaries. This method has been used successfully in studies on reptiles and amphibians to identify areas of low migration (Homola et al, 2019;Myers et al, 2019b;Chan and Brown, 2020;Burbrink et al, 2021). Modeling population structure given continuous (geographic) and discrete (reproductive isolation) processes can be used to separate clines vs. geographic clusters using programs such as conStruct (Bradburd et al, 2018).…”
Section: Identifying Geographic Lineages and Isolation By Distancementioning
confidence: 99%
“…(2) perbedaan katak dan kodok, (3) lingkup genus Rana dan Bufo, (4) amfibi sebagai hewan ovipar, dan (5) siklus hidup amfibi yang memiliki fase berudu berenang bebas di air. Banyak spesies yang ovipar dan membutuhkan air sebagai tempat pemijahan (Homola et al, 2019;Smith & Harmon, 2019), namun ada juga spesies yang ovovivipar (Iskandar et al, 2014;Sandberger-Loua et al, 2016). Demikian pula dengan metamorfosis, ada berudu dari spesies amfibi yang tidak berenang bebas di habitat perairan sebelum juvenile (Iskandar, 1998).…”
Section: Pendahuluanunclassified
“…Selain dengan komponen biotik, amfibi juga berinteraksi dengan komponen abiotik. Banyak spesies amfibi yang memanfaatkan air sebagai sumberdaya untuk melakukan tahapan metamorfosis sebelum menjadi dewasa (Homola et al, 2019). Oleh karenanya kehidupan amfibi sangat tergantung pada ketersediaan air di habitat (Brannelly et al, 2019).…”
Section: Analisis Sains Amibiunclassified